Entrance channel dynamics of hot and cold fusion reactions leading to superheavy elements - Umar, A. S.; Oberacker, V. E.; Maruhn, J. A.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2010)
We investigate the entrance channel dynamics for the reactions Zn70+Pb208 and Ca48+U238 by using the fully microscopic time-dependent Hartree-Fock theory coupled with a density constraint. We calculate excitation energies and capture cross sections relevant for the study of superheavy formations. We discuss the deformation dependence of the ion-ion potential for the Ca48+U238 system and perform an alignment angle averaging for the calculation of the capture cross section. The results show that this approach can generate results in good agreement with experiments and other theories. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2023-07-24